Human rights, plural legalities, and gendered realities : paths are made by walking paths are made by walking - Hellum, Anne.; University of Zimbabwe. Southern and Eastern African Regional Centre for Women's Law. (Harare : Southern and Eastern African Regional Centre for Women's Law, University of Zimbabwe with Weaver Press, 2007)
"This book addresses a current dilemma in the operationalization of human rights norms at state, regional and international levels, namely, the apparent failure to deliver the projected human rights benefits and protections to individuals on the ground."--BOOK JACKET.
Families and feminism : caring for mum and dad / Ann Stewart -- Kär contracts in Norway. Agreements made by men concerning women's work, ownership and lives / Tove M. Bolstad -- Working with custom. Promoting children's rights to livelihood by making de facto guardians responsible / Henrietta Wolayo Ssemmanda -- Women's burden : women, HIV/AIDS and home-based care in Zimbabwe / Ellen Sithole -- Human rights encountering gendered land and water uses. Family gardens and the right to water in Mhondoro communal land / Anne Hellum -- Making gender visible in law : Kwena women's access to power and resources / Anne Griffiths -- Following God's constitution. The gender dimensions in the Ogiek claim to Mau forest complex / Patricia Kameri-Mbote and Jacinta Anyango Oduor -- Rural women's access to landed property. Unearthing the realities within an East African setting / Rie Odgaard and Agnete Weis Bentzon -- Women's work, perceived contribution and access to land in India / Reena Patel -- Engendering the human rights protection of property rights : women's local land use in Tanzania / Ingunn Ikdahl -- I can't go to school today / Julie Stewart -- Where is the toilet? Getting down basics in accessing women's rights / Shaheen Sardar Ali -- From human development to human rights. A southern African perspective on women and teenage girls' right to reproductive choice / Anne Hellum and Anne Lene Staib Knudsen -- New fellow citizens : challenges and possibilities : implementing human rights among immigrants, the case of female circumcision in Norway / Gro Hillestad Thune -- Interpretative strategies for women's rights in a plural legal framework. Exploring judicial and state responses to Hudood laws in Pakistan / Shaheen Sardar Ali -- The widows' and female child's portion. The twisted path to partial equality for widows and daughters under customary law in Zimbabwe / Julie Stewart and Amy Tsanga -- Reconceptualizing the role of legal information dissemination in the context of legal pluralism in African settings / Amy S. Tsanga.
Includes bibliographical references and index.
Keywords: Women's rights -- Africa, Eastern; Women's rights -- Africa, Southern; Women -- Africa, Eastern -- Social conditions; Women -- Africa, Southern -- Social conditions; Women's rights; Women -- Social conditions; Women's rights; Africa, Eastern; Africa, Southern; Donation